Emotional and behavioral problems of children with phenylketonuria - Jusienė, Roma; Bieliauskaitė, Rasa; Cimbalistienė, Loreta (Psichologija, 2002)
Phenylketonuria (PKU) is an inherited genetic metabolic disorder in which the enzyme required to digest phenylanine (Phe) is missing. If untreated, individuals with PKU will develop high levels of Phe in their blood which can affect brain development and function. That's why low protein diet must be introduced as early as possible from the birth. Nevertheless, several studies show higher incidence of behavioral problems, especially internalizing, in early treated PKU children. Parental maladjustment to their child's chronic illness and everyday stress related to the burden of special diet can be reasons for psychological problems of PKU children. The aim of our study is to evaluate the psychological adjustment of PKU children (as compared to healthy controls) and analyze it in the context of psychological impact of PKU on the family.Parents of 37 early-treated PKU children (age 4-14 years old) and of 37 matched controls answered the Child Behavior Checklist (CBCL, Achenbach, 1991) and questionnaire on stress coping strategies (Elklit, 1996). Parents of PKU children also answered the questionnaire on reactions to child's disease and it's impact on the family.The results of present study indicate that PKU children have significantly more behavioral problems than healthy controls. They are more withdrawn, anxious /depressive, aggressive, have more social and attention problems. The higher rates of internalizing and overall problems are related to parental maladjustment (feelings of guilty and anger) together with maladaptive (emotional) everyday stress coping strategies. Two latter factors further indulging the child, that also predicts the psychological maladjustment of PKU children.
Keywords: emotional problems; behavioral problems; children; phenylketonuria